PENGARUH TINDAKAN KEPERAWATAN REDUKSI LUKA TEKAN TERHADAP PENURUNAN RISIKO LUKA TEKAN - Widodo, Wahyu; Rosa, Elsye Maria; Kurniasari, Novita (LPPM STIKES MUHAMMADIYAH GOMBONG, 2017)
Decubitus is a very serious problem especially for patients who hospitalized for long time with limited activity. Decubitus can increase the duration of hospital stay so that will increase the burden, especially the cost of hospitalization along with length of stay in hospital. This research of purpose to know the influences of nursing intervention to reduce pressure sore to reducing risk of pressure sore at RSU PKU Muhammadiyah Purworejo. This research design used “Pre and post test without control group